UMPSA, RUTS to explore cooperation in Engineering and Technology Programmes - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
SONGKLA, THAILAND, 19 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is set to collaborate with Rajamangala University of Technology Srivijaya (RUTS), Thailand in engineering and technology programmes as both universities are poised to sign a memorandum of understanding (MoU) soon.